2012
DOI: 10.1021/ef3010543
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Oxidation of Biodiesel by Pressurized Differential Scanning Calorimetry: Effects of Heating Ramp Rate

Abstract: Despite its many promising characteristics as an alternative diesel fuel, the oxidative stability of biodiesel during storage is a major concern to fuel producers. Extensive degradation can affect fuel quality with respect to viscosity, acid value, cetane number, and other properties. Fuel standards in the U.S. and Europe include the induction period (IP), which is designed to ensure that good quality is maintained during storage. However, IP is measured at 110 °C to accelerate the formation of radicals and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Parameter B 1 is related to the reaction activation energy, E a (kJ/mol), by E a = R g B 1 , in which R g is the gas constant. The regression analysis shows a linear correlation ( R 2 = 0.99), yielding E a = 77.8 kJ/mol, which is in agreement with the literature value for fatty acids and ester obtained by isothermal differential scanning calorimetry . The result provides a correlation for estimating OSI as a function of temperature, although an extrapolation of OSI estimation to reasonable storage temperatures is more problematic …”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Parameter B 1 is related to the reaction activation energy, E a (kJ/mol), by E a = R g B 1 , in which R g is the gas constant. The regression analysis shows a linear correlation ( R 2 = 0.99), yielding E a = 77.8 kJ/mol, which is in agreement with the literature value for fatty acids and ester obtained by isothermal differential scanning calorimetry . The result provides a correlation for estimating OSI as a function of temperature, although an extrapolation of OSI estimation to reasonable storage temperatures is more problematic …”
Section: Resultssupporting
confidence: 87%
“…The regression analysis shows a linear correlation (R 2 = 0.99), yielding E a = 77.8 kJ/mol, which is in agreement with the literature value for fatty acids and ester obtained by isothermal differential scanning calorimetry. 20 The result provides a correlation for estimating OSI as a function of temperature, although an extrapolation of OSI estimation to reasonable storage temperatures is more problematic. 19 Figure 2 presents the values of mass density, kinematic viscosity, and gross calorific value for all the samples.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore oxidation of biodiesel has attracted a lot of attention. At present, study on biodiesel oxidation almost focuses on the oxidation stability and its evaluation [2][3][4][5][6], oxidation resistance, and antioxidant [7][8][9][10][11] but the research of oxidation mechanism and characterization work is rarely reported. It is significant to fully analyze the biodiesel oxidation mechanism for improving the quality of biodiesel to accelerate the practical engineering applications of biodiesel.…”
Section: Introductionmentioning
confidence: 99%
“…Increases in the heat flow with increasing temperature were caused by changes in the chemical composition as the oil degraded. Since oxygen was used as the purge gas, initial changes were affected by oxidative degradation of the oil sample accelerated by increasing temperature .…”
Section: Methodsmentioning
confidence: 99%
“…Results from P-DSC analysis of the thermo-oxidative stability of FAME do not correlate to induction period data measured isothermally at high temperature (110°C) by a Rancimat instrument [32]. However, OT data from P-DSC are reliable in the qualitative evaluation of the relative resistance to oxidation of biodiesel (FAME) [33].…”
Section: Thermo-oxidative Stability Evaluationsmentioning
confidence: 99%